The Complete Lives of Camp People Colonialism, Fascism, Concentrated Modernity - Mrázek, Rudolf (Theory in Forms, 2020)
In The Complete Lives of Camp People Rudolf Mrázek presents a sweeping study of the material and cultural lives of twentieth-century concentration camp internees and the multiple ways in which their experiences speak to the fundamental logics of modernity. Mrázek focuses on the minutiae of daily life in two camps: Theresienstadt, a Nazi "ghetto" for Jews near Prague, and the Dutch "isolation camp" Boven Digoel-which was located in a remote part of New Guinea between 1927 and 1943 and held Indonesian rebels who attempted to overthrow the colonial government. Drawing on a mix of interviews with survivors and their descendants, archival accounts, ephemera, and media representations, Mrázek shows how modern life's most mundane tasks-buying clothes, getting haircuts, playing sports-continued on in the camps, which were themselves designed, built, and managed in accordance with modernity's tenets. In this way, Mrázek demonstrates that concentration camps are not exceptional spaces; they are the locus of modernity in its most distilled form